The Serial Tech Startup Founder (STSF) Base Theory and the Entrepreneurial Paradox - Ocsody, Peter (Journal of Strategic Innovation and Sustainability, 2020)
In order to develop a viable tech startup, generally, resilient startup venturers need to become serial startup entrepreneurs as they have to climb the learning curve through building several startups by the time a lasting business is crafted and nurtured. In this research, I intended to explore the set of qualities that helps serial tech venture founders push forward initiating startup after startup. Because of the lack of a clear understanding of this phenomenon in the current literature, I wished to inquire into this set of qualities that generates the prerequisite driving forces ensuing serial tech venturing. This research employed semi-structured video-recorded interviews to study 22 serial tech startup founders (STSF) from the Southwest Florida region. All interviews were transcribed and coded. After generating about 700 codes, I arrived at four categories (called constituent attributes) 1) Elastically Nonconforming (EN), 2) Abstracted Serial Monetizing (ASM), 3) Tech Passioning (TP), and 4) Heroed Enterprising (HE) as well as one core category called Te(ch)nacious Heroing (TcH).